The Girl Who Played With Fire: Millennium #2 - Larsson, Stieg, 1954-2004; Keeland, Reg, 1943-; Vance, Simon (New York : Random House Audio, 2009)
Two reporters responsible for a sex-trafficking exposé are murdered, and the fingerprints on the murder weapon belong to Lisbeth Salander, prompting the magazine's publisher, Mikael Blomkvist, to launch his own investigation to vindicate Salander.
Unabridged.
Compact discs.
Read by Simon Vance.
Translated from Swedish.
Keywords: Mystery fiction; Audiobooks